RETRACTED: Educational cluster environment as a criteria for professional competence development of students - Usarov J.E.; Khimmataliev D.O.; Kodirov I.D.; Ergasheva G.R.; Khamidova S.N. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001